2019
DOI: 10.1186/s12863-019-0725-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study and scan for signatures of selection point to candidate genes for body temperature maintenance under the cold stress in Siberian cattle populations

Abstract: BackgroundDesign of new highly productive livestock breeds, well-adapted to local climatic conditions is one of the aims of modern agriculture and breeding. The genetics underlying economically important traits in cattle are widely studied, whereas our knowledge of the genetic mechanisms of adaptation to local environments is still scarce. To address this issue for cold climates we used an integrated approach for detecting genomic intervals related to body temperature maintenance under acute cold stress. Our a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 49 publications
1
31
0
Order By: Relevance
“… Yang et al (2017) also identified the gene COL27A1 (found here in F ST 2 and ROH), which has been proposed to be involved in cartilage calcification, which is another important aspect in cold climates. Studying signatures of selection for candidate genes for body temperature maintenance under the cold stress in Siberian cattle populations, Igoshin et al (2019) found that the gene GRIA4 contribute to cold-stress resistance due to indirect involvement in body thermoregulation. In our study a gene from the same family ( GRIA1 ) was found for YAK in the F ST 3 and ROH scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Yang et al (2017) also identified the gene COL27A1 (found here in F ST 2 and ROH), which has been proposed to be involved in cartilage calcification, which is another important aspect in cold climates. Studying signatures of selection for candidate genes for body temperature maintenance under the cold stress in Siberian cattle populations, Igoshin et al (2019) found that the gene GRIA4 contribute to cold-stress resistance due to indirect involvement in body thermoregulation. In our study a gene from the same family ( GRIA1 ) was found for YAK in the F ST 3 and ROH scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a genomic evaluation for improved heat tolerance has been recently developed for Australian dairy cattle ( Nguyen et al, 2016 ). There is an increased interest in identifying and exploring signatures of selection (also known as selective sweeps) and the genomic diversity resulting from adaptation to environment and artificial selective pressure ( Igoshin et al, 2019 ; Osei-Amponsah et al, 2019 ; Upadhyay et al, 2019 ). Different approaches can be used to scan the genome for regions of homozygosity, as well as to estimate differences in the frequency of alleles or haplotypes between divergent populations or even generations within a population ( Boschiero et al, 2018 ; Ceballos et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…From the multivariate envGWAS in Red Angus, 9 of the 16 positional candidate genes have been identified by previous studies of adaptation or selection in humans or cattle (DIRC1, ABCB1, TBC1D1, AP5M1, GRIA4, LRRC4C, RBMS3, GADL1, PLA2G12B) 89,113,114 . For example, GRIA4 has been identified as a target of selection in coldadapted Yakutian cattle populations 115 . Of the other 7 candidate genes, three have been previously associated with adaptive phenotypes; body size (E2F7, BBS1) and circadian rhythm (ADCYAP1).…”
Section: Envgwas Detects Variants Segregating Along Continuous Enviromentioning
confidence: 99%
“…After detection of significant and suggestive SNPs, the positions of SNPs on the chicken reference genome (Gallus-Gallus 4.0) were identified by NCBI database. According to Yates et al (2015), the names of the genes in 250 kbp up and down regions of significant SNPs were detected from NCBI and Ensembl (Goor et al 2015;Mengmeng et al 2016;Igoshin et al 2019). In order to investigate molecular and biological functions of the identified candidate genes, the UniProt (Universal Protein Resource) database was searched (Pundir et al 2015) and the animal QTLdb database was used for finding the QTL in the candidate genomic regions (Hu et al 2015).…”
Section: Post-gwas Analysismentioning
confidence: 99%